Low physical activity is associated with adverse health outcome and higher costs in Indonesia: A national panel study - Anindya, Kanya; Marthias, Tiara; Zulfikar Biruni, Muhammad; Hage, Sophia; Ng, Nawi; Laverty, Anthony A.; McPake, Barbara; Millett, Christopher; Haregu, Tilahun Nigatu; Hulse, Emily S. G.; Cao, Yingting; Lee, John Tayu (Frontiers in Cardiovascular Medicine, 2022)
Aims: To assess the association between low physical activity, cardiovascular disease (CVD) and risk factors, health service utilization, risk of catastrophic health expenditure, and work productivity in Indonesia. Methods: In this population-based, panel data analysis, we used data from two waves of the Indonesian Family Life Survey (IFLS) for 2007/2008 and 2014/2015. Respondents aged 40–80 years who participated in both waves were included in this study (n=5,936). Physical activity was assessed using the International Physical Activity Questionnaire (IPAQ-SF). Multinomial logistic regression model was used to examine factors associated with physical activity levels (low, moderate, and high). We applied a series of multilevel mixed-effect panel regression to examine the associations between physical activity and outcome variables. Results: The prevalence of low physical activity increased from 18.2% in 2007 to 39.6% in 2014. Compared with those with high physical activity, respondents with low physical activity were more likely to have a 10-year high CVD risk (AOR 2.11, 95% CI 1.51–2.95), use outpatient care (AOR 1.26, 95% CI 1.07–1.96) and inpatient care (AOR 1.45, 95% CI 1.07–1.96), experience catastrophic health expenditure of 10% of total household expenditure (AOR 1.66, 95% CI 1.21–2.28), and have lower labor participation (AOR 0.24, 95% 0.20–0.28). Conclusions: Low physical activity is associated with adverse health outcomes and considerable costs to the health system and wider society. Accelerated implementation of public health policies to reduce physical inactivity is likely to result in substantial population health and economic benefits.